Implementasi Animasi Stop-motion untuk Mengembangkan Penguasaan Konsep Energi Siswa SMP pada Pembelajaran IPA - Fadelia Amanda Putri Andhika (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Many concepts in science learning, such as the concept of energy, were abstract and could not be observed directly. This required teaching methods that effectively conveyed these abstract ideas. This research explored how students' creation of Stop-Motion Animation helped in developing their mastery of energy concepts. The research used a qualitative case study approach and collected data through semi-structured interviews, which were then analyzed thematically. The research methodology involved five stages: introduction, introduction to the phenomenon, storyboarding, animation creation, and discussion. The findings showed that students' engagement in stop-motion animation facilitated the development of their mastery of the concept of energy. The results showed that the number of mentions and conceptual representations made by students on the concept of forms of potential energy was 40 times, the concept of forms of kinetic energy was 30 times, the concept of quantity was 22 times, the concept of value change was 34 times, the concept of transfer/transformation was 10 times, and the concept of conservation was 15 times. Based on the results of the analysis, it could be concluded that through the creation of Stop-Motion Animation, students were able to develop mastery of the concept of energy. Of the five aspects of the energy concept, stop-motion animation contributed greatly to the concept of Form and the concept of Value Change, but little or less to the concept of Transfer/Transformation.
Reuploud Repository hasyim Juni 2026 Approved by Teddy
Keywords: Concept mastery; Stop-motion Animation; Energy; Science Learning